The Relationship Between Instagram's Social Media Marketing Activities and Customer Loyalty In The Mediation of Value Equity and Relationship Equity In Kopinkra Batik Girli Products Kliwonan, Masaran District Sragen Regency - Zailani, Abdullah (Journal of Advances in Accounting, Economics, and Management, 2025)
The objectives of this study wre: 1) To test and measure the influence of Instagram Social Media Marketing Activities (SMMA) on Customer equity drivers (CEDs). (2) To test and measure the influence of Customer equity drivers (CEDs) on consumer loyalty (3) To test and measure the influence of Instagram SMMA through CEDs as a mediating variable. This study was conducted on batik customers at the Batik People's Craft Industry Cooperative (Kopinkra Batik Girli) Kliwonan, located in Masaran District, Sragen Regency. The population in this study were all customers who had purchased and knew about Kopinkra Batik Girli Kliwonan Sragen products through Instagram. A sample of 115 respondents was taken by purposive sampling. The results of the study found that there was an influence of Instagram SMMA on CEDs consisting of relationship equity and value equity. Instagram SMMA had an effect on customer royalty. There was an indirect influence of the relationship between Instagram SMMA and customer royalty through mediation, namely relationship equity. There was no indirect influence of the relationship between Instagram SMMA and customer royalty through mediation, namely value equity.